Failure Assessment of Steel-Concrete Composite Column Under Blast Loading - BUDZIAK, Marcin P.; GARBOWSKI, Tomasz (Engineering Transactions, 2014)
Composite column as a key structural member can be subjected to a blast load as a result of an accident or a terrorist threat. In this paper, a method for assessing the blast resistance of a composite concrete-filled column is proposed. Moreover, different methods of enhancing composite member resistance to explosions are investigated. The blast situation is modeled in the FEM software using the CONWEP tool. This empirical formulation is relatively cheap from the computational point of view, as well as precise enough, hence it was chosen for this work purposes. Material models are based on well known elasto-plastic with linear hardening concepts. Important phenomenons are also taken into account, such as: contact formulation between the column components, strain rate dependence, damage initiation and evolution. Simulations are conducted for the most common type of explosion – surface blast. Its main feature is the effect of reflection of the ground surface and hence, amplification of the blast wave after the charge ignition. Results are presented in terms of minimum TNT mass equivalent required for a column member failure.